(untitled) (Comprehensive Journal of Science, 2025)
A study was conducted to investigate the occurrence of high gold grades in a carbon fine collected from the gold recovery circuit in a gold Mine. The research revealed that fine magnetic particles present in the overflow from the carbon fines tank contained significantly elevated gold concentrations, in the range from 2,000 to 7,000 g/t, with the -37 micron fraction reaching values as high as 17,000 g/t. Scanning electron microscopy (SEM) analysis showed that gold was adhered to the surfaces of iron particles. The objective of the investigation was to identify the processes responsible for gold attachment to magnetic iron particles and to propose process modifications to minimize gold losses within the carbon circuit. Various samples from the gold recovery circuit solids and solutions were collected and analyzed. There are two potential mechanisms proposed: gold cementation onto iron surfaces, and heterocoagulation of colloidal gold with iron oxides within the elution column. The separation of gold from the cathode in the electrowinning (EW) cell and the reduction of the gold–cyanide complex to metallic gold in the carbon regeneration kiln were identified as a potential source of colloidal gold. SEM–EDX analysis further indicated that the main sources of iron were natural magnetite and roasted iron sulfides. The formation of dendritic gold within the carbon regeneration kiln is believed to occur through thermal reduction of gold.